2017
DOI: 10.1002/celc.201700320
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Controlled Hollow Spheres of C/α‐Fe2O3 Prepared through the Quasiemulsion‐Templated Method and Their Electrochemical Properties for Lithium‐Ion Storage

Abstract: In this paper, α‐Fe2O3 hollow spheres in different sizes were successfully synthesized through a glycerol emulsion template method for use as efficient electrode materials in lithium‐ion batteries. The sizes of α‐Fe2O3 hollow sphere could be easily controlled by adjusting the amount of glycerol over the Fe precursor during the hydrothermal synthesis process. A thin carbon layer was subsequently coated on the surface of α‐Fe2O3 hollow spheres through hydrothermal treatment with glucose for the carbonization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Initial columbic efficiency is 66.8 %. The irreversible capacity is due to decomposition of electrolytes and consequent formation of solid electrolyte interface (SEI) layer . As shown in Figure S6, the GCD curves under different current densities keep a similar shape and delivered high capacity, suggesting the good rate performance of the Fe 2 O 3 ‐NPs@CNT composite.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…Initial columbic efficiency is 66.8 %. The irreversible capacity is due to decomposition of electrolytes and consequent formation of solid electrolyte interface (SEI) layer . As shown in Figure S6, the GCD curves under different current densities keep a similar shape and delivered high capacity, suggesting the good rate performance of the Fe 2 O 3 ‐NPs@CNT composite.…”
Section: Resultsmentioning
confidence: 48%
“…reported an ultrahigh reversible capacity of 2071 mAh g −1 for the encapsulated Fe 2 O 3 nanoparticles in CNTs at 0.05 A g −1 . It should be mentioned that the reported 2545 mAh g −1 by this research occupies the highest lithium storage capacities reported for Fe 2 O 3 at present, which can be attributed to the above‐mentioned capacity enhancing mechanism ,,,…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…To overcome the intrinsic disadvantages of Fe 2 O 3 , intensive efforts have been devoted to the fabrication of novel micro/nano‐structures and synthesis of various nanocomposites. In particular, the fabrication of porous structural electrodes has proven to be a suitable strategy for LIBs . Recently, many studies have reported the synthesis of Fe 2 O 3 with hierarchical porosity and unique microstructure, such as hollow spheres and cubes,, Fe 2 O 3 @N−C hollow nanoparticles, hollow nanobarrels α‐Fe 2 O 3 /rGO, 3DG/Fe 2 O 3 aerogel, 3D hierarchical porous α‐Fe 2 O 3 nanosheets, and porous Fe 2 O 3 @C rods .…”
Section: Introductionmentioning
confidence: 99%